End Point of Multivalued Cyclic Admissible Mappings: Binayak S. Choudhury, Nikhilesh Metiya, Sunirmal Kundu - Team, Support (Thai Journal of Mathematics, 2022)
In this paper we introduce an admissibility condition for multivalued mappings. Also we introduce two types of multivalued almost contractions with the help of δ- distance. We show that these contractions, under the assumption of the admissibility condition defined here, have end point property. The results are obtained without any reference to continuity. There is also an illustrative example.